Pengaruh Sikap Belajar Terhadap Kemampuan Komunikasi Matematis Siswa Kelas VIII SMP Negeri 43 Merangin - Rais, Hidayati; Hasmawati, Hasmawati; Ningsih, Lipia Sepna (JURNAL PEMBELAJARAN DAN MATEMATIKA SIGMA (JPMS), 2021)
The mathematical communication ability of students is still low, is known from the results of the initial test that there are no students who meet learning mastery. Because students have not mastered and are ability to apply all indicators of mathematical communication skills. The purpose of this research is to describe the significant influence between learning attitudes on mathematical communication skills. This research uses a quantitative approach to the correlational method. The population of this research is all students of class VIII SMP N 43 Merangin consisting of 4 classes totaling 120 people. For the sample using the Taro Yamane formula, 55 people were selected, the sampling method used was simple random sampling with the lottery method. The data collection technique used questionnaire and test data. The instrument used in the form of statement items and items about mathematical communication skills. Based on the data analysis technique, the data obtained are normally distributed and have a linear pattern. Furthermore, to test the hypothesis using the Pearson product moment formula, and the significance test using the Z-test, followed by the determinant coefficient formula for variable X to variable Y from the analysis is known that the coefficient of determination is 27.35%. Then a simple linear regression test and a regression significance test were performed. Based on the results of data analysis, it shows that if Fcount > Ftable or 19.948 > 1.907, then H0 is rejected and H1 is accepted, meaning that there is a significant influence between learning attitudes on the mathematical communication skills of eighth grade students of SMP N 43 Merangin.Keywords: Learning Attitude, Mathematical Communication Ability